Ceruloplasmin and antioxidative enzymes in pre-eclampsia. (16th September 2016) - Nikolic, Aleksandra; Cabarkapa, Velibor; Novakov Mikic, Aleksandra; Jakovljević, Ana; Stosic, Zoran
Abstract: Objective : To evaluate diagnostic value of ceruloplasmin together with other enzymatic and nonenzymatic antioxidants (superoxide dismutase (SOD), glutathione peroxidase (GSH-Px) and uric acid) and to evaluate the level of oxidative stress in patients with pre-eclampsia (PE) and compare it with normal pregnancy. Methods : In this prospective study, antioxidative markers were investigated in two groups of pregnant women: patients with pre-eclampsia ( n = 32) and the healthy pregnant women ( n = 60). The following antioxidative markers and enzymes were evaluated: serum ceruloplasmin levels, uric acid, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). Results : Serum levels of ceruloplasmin, uric acid and SOD were significantly higher in the PE group compared to the control group. Serum levels of GSH-Px were not significantly higher in the PE group compared to the control group. Serum ceruloplasmin and serum uric acid have the best diagnostic accuracy for oxidative stress in PE and are more accurate compared to antioxidative enzymes -SOD and specially more accurate than GSH-Px. Conclusions: Serum ceruloplasmin level may have significant role as the markers of oxidative stress in pre-eclampsia especially when used in combination with uric acid levels.